Toward sustainable and equitable development : sector strategies for Latin America and the Caribbean (IDB WashingtonUS, 2004)
Presents seven sector strategies which are a set of guidelines for the activities of the Inter-American Development Bank and its borrowing countires. Seeks, by these guidelines, to confront the principal limitations to achieving sustainable economic growth, reducing poverty and promoting social equity.
Keywords: SUSTAINABLE DEVELOPMENT